A Rare Case of Metastatic Malignant Melanoma to the Colon from an Unknown Primary. (30th June 2014) - Reddy, Preethi; Walker, Courtney; Afonso, Bianca
Abstract : Metastatic melanoma from an unknown primary (MUP) is rare; its occurrence in the gastrointestinal tract is of exceedingly low prevalence. We report a case of a 73-year-old man with metastatic malignant melanoma to the colon from an unknown primary. The rarity of MUP and importance of screening for gastrointestinal metastasis in patients with malignant melanoma are discussed along with the role of surgical resection in improving prognosis and overall survival.